Outcomes and eye care knowledge in rhegmatogenous retinal detachment patients with a history of laser refractive surgery for myopia - Lan, Chieh; Chen, Yi-Hao; Chen, Yung-Jen; Lee, Jong-Jer; Kuo, Hsi-Kung; Wu, Pei-Chang (Frontiers in Public Health, 2022)
Purpose To investigate the surgical outcomes and eye care knowledge of patients with rhegmatogenous retinal detachment (RRD) who had previously undergone laser refractive surgery (LRS) for myopia in a myopia epidemic area. Methods This retrospective study included patients with primary RRD who underwent surgery and had a history of LRS for myopia at a tertiary medical center. Data were reviewed from medical charts to analyse the surgical outcomes. Questions about eye care knowledge and attitude toward myopia and LRS were obtained. Results A total of 774 patients underwent RRD surgery, among whom 341 (44%) had myopia greater than -3 dioptres, 66% of whom had high myopia. Thirty eyes of 26 patients had a history of LRS for myopia. The mean age of patients with a history of LRS was significantly lower than that of those without a history of LRS (45.7 ± 2.9 years vs. 53.8 ± 1.0, p < 0.001). The mean pre-LRS spherical equivalent was -8.66 ± 0.92 dioptres. In more than half the patients (n = 15, 57.7%), the interval between LRS and RRD was more than 10 years. The primary retinal reattachment rate was only 60%, whereas the final retinal reattachment rate was 93%. The mean final visual acuity (VA) improved from 20/286 to 20/105 (p = 0.006). Linear mixed model analysis showed factors of male sex and macular detachment were significant with poor visual outcome (p=0.046 and 0.008) Eye care knowledge obtained from the 19 RRD patients with a history of LRS, 47% of patients (9/19) mistakenly thought that LRS could cure myopia and its complications, and 63% of patients were less willing to visit an ophthalmologist because of uncorrected VA improvement after LRS. Eighty-four percent thought that proper knowledge and more education about LRS and myopia for the public are important. Conclusion The age of RRD patients with a history of LRS for myopia was relatively younger. Male sex and macular detachment were associated with poor visual outcomes. More education with proper knowledge of LRS, myopia, and RRD is recommended for the patients to prevent or early detect the occurrence of RRD.